Kepemimpinan Spiritual dalam Lembaga Pendidikan: Analisis Maqasid Syariah - Millah, Nur Ita A’ini Qudwatal; Far’ia (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
Leadership in an educational institution is one of the determining factors in the success of an educational institution. Through a good system and pattern of leadership, educational institutions will be able to know where they want to go and reach clearly. Spiritual intelligence is needed for a leader to lead an educational institution, especially Islamic educational institutions. In the scope of leadership based on spiritual values, the orientation of all its activities is as a manifestation of worship and a means of devotion to God. Therefore, the journal discusses the concept of spiritual leadership in Islamic educational institutions Maqashid Sharia perspective in terms of dharuriyyat starting from the side of hifdz al-din, hifdz al-nafs, hifdz al-aql, hifdz al-nasl and hifdz al-mal and its implementation in the Da'wah Management Study Program of UIN Sunan Kalijaga Yogyakarta. This research uses descriptive qualitative study methods. Data collection techniques using observation, interviews and documentation. The results showed that the head of the department in this study program had a main program in education and training as part of the development of spiritual leadership. Through this case, the head of the department and the lecturer do not simply abort the administrative obligations, namely to carry out the learning process, but also as a means of devotion to God. In addition, spiritual leadership is demonstrated through exemplary efforts to the characteristics of the Prophet, namely siddiq, amanah, tabligh, and fathanah as well as various forms of policies implemented by the Chair of the Department aiming to achieve mutual benefit.